Measuring student success using the High-Impact Practices Spectrum: Evidence for the value of High Engagement Experiences - Dianne Murphy; Heather Kaminski; Kathryn Marten (Journal of the Scholarship of Teaching and Learning, 2025)
The HIPs Spectrum is a taxonomy for assessing and categorizing courses along a continuum based on elements of High Impact Practices (Author et al., under review). This study provides quantitative evidence for the validity and impact of the HIPs Spectrum by analyzing seven years of enrollment data in a Midwestern regional comprehensive university School of Business. We additionally provide theoretical support for the HIPs Spectrum using Self-Determination Theory (Ryan & Deci, 2017). Along the HIPs Spectrum, courses are categorized as High Impact Practice (HIP), High Engagement Experience (HEE), or Neither. Labeling the medium-intensity HEE courses allows for a detailed analysis of their effect on students, which is a gap in previous literature. Results show supportive evidence for both HIP and HEE courses significantly increasing student persistence, and HEEs significantly decreasing time to graduation in comparison with Neither courses. Students earned an average of half a letter grade higher in HIP courses than in Neither courses. Surprisingly, HEE courses had a larger positive effect on students than HIP courses for some variables, justifying the importance of researching and implementing HEEs as a pedagogical tool to support student success. Classification of courses along the HIPs Spectrum is now an important step in accurate measurement of how engaged learning affects students. As the HIPs Spectrum grows in use, it could shift how we classify, measure, and evaluate courses under the umbrella of High-Impact Practices.